Village Environmental Planning as an Effort in Revitalizing Tourist Destinations - Intan Permata Hati; Fathan Prayana Putra; Lale Haydi Megaviana; I Gusti Anindita Hendryanadewi; Indira Tri Prajarani; Dimas Firmansyah; Akbar Adiguna; Muhammad Rifqi; Zamroni Alpian Muhtarom (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
Village Development Activities (MBKM) is a program that is closely correlated with student service to a village or region by applying and developing the knowledge they have acquired during their studies. Problems related to the lack of public awareness of the tourism potential in East Kuripan Village are also issues that are often faced by the Village Head and his staff, such as there is no infrastructure to support the tourism potential so that the community cannot explain to tourists about the tourism potential in the village. One of the concrete steps taken is making tourist signs and planting plant seeds. The aim of making tourist signs is to provide clear information and make navigation easier for visitors, so that they can explore the various tourism potentials that exist in the village. Meanwhile, planting of plant seeds is carried out to beautify the village environment, improve air quality, and create a more beautiful and cool atmosphere. These two efforts are expected to increase tourists' interest in visiting, extend the duration of visits, and ultimately improve the village economy through the tourism sector.